Orthogeriatric co-management – managing frailty as well as fragility. Issue 8 (August 2018) - Pioli, Giulio; Bendini, Chiara; Pignedoli, Paolo; Giusti, Andrea; Marsh, David
Abstract: A high proportion of patients with fragility fracture, mainly hip fracture, have a variable degree of comorbidity and show some degree of dependence in basic or more complex activities of daily living. Evaluating these patents following the geriatric concept of frailty, about one third of hip fracture patients may be categorised as frail with high risk of poor outcomes and prolonged length of stay, one third as not frail, and about one third with an intermediate condition. Due to the high vulnerability, combined with the hip fracture event and surgical repair procedures, a multidisciplinary approach that includes geriatric competencies becomes essential to improve short and long-term outcomes after hip fracture. A key element of an effective process of care is a true co-managed approach that applies quality standards and provides a fast-track pathway of care, minimises the time the patient spends in bed, and reduces postoperative complications by means of standardised procedures. The occurrence of a fragility fracture is the strongest risk factor for a subsequent fracture. Moreover, frail subjects have a further risk of fracture due to high risk of falls − related to loss of muscle mass, multiple illnesses, impaired balance and weakness. Thus, effective secondary prevention strategies are essential to reduce morbidity and mortality after hip fracture, and they are currently a standard task of orthogeriatric care. Fracture liaison services (FLS) are probably the most efficient way of addressing secondary prevention including the assessment of both bone health and falls risk. Therefore, the optimal management of frail patients with fragility fracture includes both orthogeriatric care and FLS, which are complementary to each other. Orthogeriatric collaboration is also powerful in influencing healthcare policy. British experience as well as that in Ireland, Australia and New Zealand, have shown that when two widely disparate specialisms say the same thing, they may achieve a fundamental shift in attitudes and behaviour of both managers and clinicians. Furthermore, a continuous real-time audit, at national level, is a powerful driver for change and better standards of care.